TRANSMURAL MIGRATION OF SURGICAL SPONGE INTO CECUM: A RARE CASE REPORT - R. Omranipour; M. R. Farahm A. Arab-Kheradm (Acta Medica Iranica, 2006)
Retained foreign body in the abdominal cavity following surgery is a continuing problem. We report a case of an 18 year old man who was referred with abdominal pain and cecal mass. Clinical exam, computed tomography scan and colonoscopy were suggestive of cecal tumor. Laparotomy confirmed a retained surgical sponge which had migrated from peritoneal cavity into cecum.